Contrasting the physiological effects of heliox and oxygen during exercise in a patient with advanced COPD. Issue 3 (September 2019) - Louvaris, Zafeiris; Vogiatzis, Ioannis
A 64-year-old man with a history of long-term cigarette smoking (>36 pack-years) and diagnosis of chronic obstructive pulmonary disease (COPD) (forced expiratory volume in 1s (FEV1 ): 47% predicted; FEV1 /forced vital capacity: 61% predicted) was referred to an outpatient pulmonary rehabilitation programme [1]. The patient exhibited gas trapping at rest (residual volume/total lung capacity (TLC): 167% predicted; inspiratory capacity (IC)/TLC: 29%) and reported exertional dyspnoea at grade 3 on the 1–5 Medical Research Council scale [2]. The patient's medication included bronchodilators and inhaled steroids. The patient poorly tolerated the cardiopulmonary exercise test (sustained at 75% of his peak exercise capacity, WRpeak). This was demonstrated by substantially reduced endurance time (6 min 30 s), profound dynamic hyperinflation (reduction in IC from rest by 232 mL), moderate exertional hypoxaemia (arterial oxygen saturation measured by pulse oximetry ( S pO2 ) 87%) and reported severe breathlessness as the predominant reason for terminating exercise ( i.e. score of 8 on the 1–10 Borg scale [3]) (table 1). In COPD patients the ergogenic effect of heliox or oxygen breathing might be related both to improvements in ventilatory parameters (that lessen dyspnoea) and to enhanced oxygen delivery to respiratory and locomotor muscles http://bit.ly/2JlJBTc